Standard therapies: solutions for improving therapeutic effects of immune checkpoint inhibitors on colorectal cancer - Liang, Tingting (Oncoimmunology, 2020)
Immunotherapy using immune checkpoint inhibitors has opened a new era for cancer management. In colorectal cancer, patients with a phenotype of deficient mismatch repair or high microsatellite instability benefit from immunotherapy. However, the response of rest cases to immunotherapy alone is still poor. Nevertheless, preclinical data have revealed that either ionizing irradiation or chemotherapy can improve the tumoral immune milieu, because these approaches can induce immunogenic cell death among cancer cells. In this regard, combination use of standard therapy plus immunotherapy should be feasible. In this review, we will introduce the specific roles of standard therapies, including radiotherapy, chemotherapy, antiangiogenic and anti-EGFR therapy, in improving therapeutic effect of immune checkpoint inhibitors on colorectal cancer.